EVENT MARKETING STRATEGY TO INCREASE SALES USING THE CONCEPT OF PURPOSE, PEOPLE, PLACE, AND PERFORMANCE (International Journal of Cultural and Social Science, 2026)
Event Marketing Strategy is an important pillar in introducing products directly and building emotional relationships between brands and consumers, especially in the automotive industry. This study uses Qualitative Research. The informants of this study amounted to 17 people. This study aims to analyze how Event Marketing Strategy in Increasing Sales by Using Purpose, People, Place, and Performance, especially for BMW and MINI products offered by PT. Performance Motors Indonesia. Event Marketing Strategy in Increasing Sales by Using Purpose, People, Place, and Performance, especially for BMW and MINI products offered by PT. Performance Motors Indonesia. The conclusion of the study, Event Marketing Strategy has a very significant contribution in driving increased sales, especially in the premium automotive industry such as BMW, Quantitatively, Event Marketing's contribution to sales achievement is estimated to reach 60-70 percent, the attractiveness of the product itself, competitive pricing structure, the image of exclusivity attached to the BMW brand, and the level of brand awareness among target consumers. The recommendation from this study is, the Company needs to improve integration between the Marketing team and the Sales team in the process of designing and implementing Events